Malignancy risk associated with diagnostic categories defined by the Papanicolaou Society of Cytopathology pancreaticobiliary guidelines. Issue 6 (11th December 2013) - Layfield, Lester J.; Dodd, Leslie; Factor, Rachel; Schmidt, Robert L.
<x xml:space="preserve">Abstract</x> BACKGROUND Endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) is currently the predominant method for obtaining a preoperative tissue diagnosis for pancreatic lesions suspicious for malignancy. The diagnostic sensitivity and specificity of EUS‐FNA are well documented, but malignancy risk associated with the diagnostic categories proposed by the Papanicolaou Society of Cytopathology is poorly defined. METHODS The records of the Departments of Pathology at Duke University and the University of Utah were searched for all cases of EUS‐FNA performed for the investigation of pancreatic lesions. All cases with follow‐up surgical diagnosis or greater than 3 years of clinical follow‐up were selected. Cytologic diagnostic categories were "nondiagnostic, " "benign, " "atypical (not otherwise specified), " "suspicious for malignancy, " "neoplasm, " and "malignant." Correlation of cytologic diagnosis with surgical and/or clinical follow‐up was made and risk of malignancy calculated for each category. RESULTS Three hundred seventeen EUS‐FNAs with adequate surgical or clinical follow‐up were obtained. Risk of malignancy for nondiagnostic specimens was 21%;, benign specimens, 13%; atypical cases, 74%; suspicious for malignancy, 82%; the neoplasm category, 14%; and the malignant category, 97% CONCLUSIONS The cytologic categories proposed by the Papanicolaou Society of Cytopathology demonstrate an increasing risk for malignancy extending from benign to malignant. Aspirates designated benign have the lowest risk of malignancy (13%) and aspirates designated malignant the highest (97%). The proposed categorization scheme stratifies risk for malignancy giving useful information to clinicians treating patients with pancreatic lesions. Cancer (Cancer Cytopathol) 2014;122:420–427. © 2013 American Cancer Society.